PRINCIPAL'S PERCEPTIONS OF STUDENTS' USE OF BORN BY PISA 2018 - Safari Safari (Akademika : Jurnal Teknologi Pendidikan, 2021)
The main objective of this study is to answer the following questions. Is there a relationship between the principal's perception of the use of liquor by students with sports teams, school drama / music groups, and band / choir groups based on PISA 2018. The research method used is quantitative method. The data in this study uses PISA 2018 data that has been released to the public and has been permitted to be used for research development purposes. The population of this study were principals in schools where 15-year-old students were studying in 2018, while the sample was principals in schools where 15-year-old students took PISA tests in 80 countries. The reason for choosing the sample was the principal in the school where the student was taking the 2018 PISA test. The data in this study were in the form of a questionnaire that was answered by principals in 80 countries, namely 20811 principals from 80 countries. Based on the results of the multiple regression analysis, the results show that there is a relationship between the principal's perception of the use of alcohol by students with sports teams, school drama / music groups, and band / choir groups based on PISA 2018 (P <0.000). The reliability of the instrument is 1.00 higher than the reliability of the person = 0.04. The conclusion is that statistically there is a relationship between the principal's perception of the use of alcohol by students with sports teams, school drama / music groups, and band / choir groups based on PISA 2018. These results indicate that the lower the use of alcohol and drugs in students at school, the more successful the school sports team, school drama/music group, and school band/choir group or vice versa.